Drug coated balloon supported Supera stent versus Supera stent in intermediate and long-segment lesions of the superficial femoral artery: 2-year results of the RAPID Trial - Boer, Sanne W. de; Böckler, Dittmar (The journal of cardiovascular surgery, 2019)
BACKGROUND: Endovascular treatment of occlusive disease of the superficial femoral artery (SFA) has evolved from plain old balloon angioplasty (MBA) through primary stenting strategy to drug eluting technology-based approach. The RAPID Trial investigates the added value of drug coated balloons (DCB, Legflow) in a primary stenting strategy (Supera stent) for intermediate (5-15 cm) and long segment (>15 cm) SFA lesions. METHODS: In this multicenter, patient-blinded trial, 160 patients with intermittent claudication, ischemic rest pain, or tissue loss due to intermediate or long SFA lesions were randomized (1:1) between Supera + DCB and Supera. Primary endpoint was primary patency at 2 years, defined as freedom from restenosis on duplex ultrasound (peak systolic velocity ratio <2.4). RESULTS: At 2 years, primary patency was 55.1% (95% CI: 43.1-67.1%) in the Supera + DCB group versus 48.3% (95% CI: 35.6-61.0%) in the Supera group (P=0.957). Per protocol analysis showed a primary patency rate of 60.9% (95% CI: 48.6-73.2%) in the Supera + DCB group versus 49.8% (95% CI: 36.9-62.7%) in the Supera group (P=0.469). The overall mortality rate was 5% in both groups (P=0.975). Sustained functional improvement was similar in both groups. CONCLUSIONS: The 2-year results in the current trial of a primary Supera stenting strategy are consistent with other trials reporting on treatment of intermediate and long SFA lesions. A DCB supported Supera stent strategy did not improve patency rate compared to a Supera stent only strategy.